ANALISIS INDEKS KEPUASAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PERTAMINA EP DI KECAMATAN BUNYU KABUPATEN BULUNGAN KALIMANTAN UTARA - Sekar Inten Mulyani; Budi Rosen Nover Saragih; Karina Austrina Putri; Frisca Ririn Amelia (Universitas Borneo Tarakan, 2022)
The people's livestock program is one of PT Pertamina EP Asset 5's CSR (Corporate Social Responsibility) programs in the field of community empowerment agriculture. This program aims to empower farmers to carry out sustainable broiler farming activities. The research objectives are 1). To know the characteristics of CSR program breeders and 2) To analyze the CSR program satisfaction index. This research was conducted in the Harapan Baru Farmers Group, Bunyu District, Bulungan Regency, North Kalimantan. Implementation time from May to July 2021. The level of farmer satisfaction was analyzed using the Customer Satisfaction Index (CSI) with five dimensions of service quality, namely tangibles (physical evidence), Empathy (Empathy), Reliability (Reliability), Responsiveness (Responsiveness) and Assurance (Guarantee). The measurement of the level of satisfaction with the service quality of the CSR program uses a Likert scale based on scores. Characteristics of livestock CSR program respondents aged 63-70 years (44.44%), junior high school education (44.44%), farming experience 14-22 years (33.33%) and livestock farming experience 2-3 years (77.78%). Physical evidence can be seen from the satisfaction of farmers from livestock cultivation facilities and infrastructure provided in the CSR program as needed. Empathy from technical officers and CSR assistants in conducting technical guidance. Reliability in providing innovation and technical information on livestock, quickly responding and providing solutions to group problems and guaranteeing the sustainability of the CSR program. The results of the CSI (Customer Satisfaction Index) score reached 82.95 in the very satisfied category (80-100). CSI was measured by the value of MIS (Mean Importance Score), MSS (Mean Satisfaction Score), WF (Weight Factors), WS (Weight Score).